The Swedish external position and the Krona - Philip R. Lane (Sveriges Riksbank, 2006)
This paper addresses the dynamics of the Swedish external position, with a particular focus on its inter-relation with the external value of the krona. We argue that financial globalisation means that a broader conceptual framework is required, whereby exchange rate fluctuations operate through the 'valuation channel' of external adjustment, in addition to the traditional trade balance channel. In the other direction, we highlight that the projected trend for the trade balance is an important influence on the long-term prospects for the krona. Finally, we seek to assess the future direction for the Swedish net foreign asset position by investigating the likely impact of demographic change and shifts in the Swedish position in the world income distribution.
Keywords: F0; F2; F3; 330; real exchange rate; external adjustment; Sweden; Globalisierung; Internationaler Finanzmarkt; Zahlungsbilanz; Wechselkurs; Schweden